PUBLIC PERCEPTION OF PEDESTRIAN SPACE IN INDUSTRIAL ZONES: A CASE STUDY OF THE PULOGADUNG INDUSTRIAL ZONE - Merinda, Herlina; Hasibuan, Hayati Sari; Tumuyu, Sri Setiawati (International Review of Humanities Studies, 2026)
Addressing the difficulties of sustainable development, the Jakarta Industrial Estate Pulogadung encounters the challenge of becoming more inclusive in constructing infrastructure for walkers by creating paths that are friendly for pedestrians As walking serves as an important sustainable and healthful means of transport, having pedestrian pathways can enhance how the public views pedestrian accessibility in their workplace. This, in turn, can promote the use of more eco-friendly public transport options. This research aims to explore how the public views pedestrians in industrial zones, with the goal of promoting spaces that are friendly to walkers. The study utilized a quantitative method paired with a mixed-methods analysis, which comprised observations, interviews, surveys, and spatial assessments. The Walkability Index measured at JIEP was recorded as 62.46, which is categorized as "waiting for walking." This designation suggests that the JIEP Industrial Area holds significant potential for transformation into an area that supports pedestrians, particularly by incorporating green corridors and adequate facilities along roadways. The objective of this article is to highlight the significance of designing industrial areas to create a more comfortable and pedestrian-friendly atmosphere, informed by observations of pedestrian experiences.